Geo-Spatial Information for Managing Ambiguity - Senthil Kumar M.; V. Mathivanan (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
An innate test emerging in any dataset containing data of space as well as time is vulnerability due to different wellsprings of imprecision. Incorporating the effect of the instability is a principal while evaluating the unwavering quality (certainty) of any question result from the hidden information. To bargain with vulnerability, arrangements have been proposed freely in the geo-science and the information science look into group. This interdisciplinary instructional exercise crosses over any barrier between the two groups by giving an exhaustive diagram of the distinctive difficulties required in managing indeterminate geo-spatial information, by looking over arrangements from both research groups, and by distinguishing likenesses, cooperative energies and open research issues.